Adsorption-enhanced nickel-based catalyst, preparation method thereof and application of adsorption-enhanced nickel-based catalyst in low-temperature CO2 methanation
By using a combination of mesoporous yttrium oxide support and metal nickel salt, an adsorption-enhanced nickel-based catalyst was prepared, which solved the problem of insufficient activity and stability of low-temperature CO2 methanation reaction, and achieved efficient CO2 conversion and stable catalytic performance.
Patent Information
- Application Number
- CN202411645751.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The prior art is difficult to effectively improve the activity and stability of the CO2 methanation reaction under low temperature conditions, and the metal nickel salt is prone to sintering at high temperatures, resulting in poor catalyst stability.
Mesoporous yttrium oxide is used as a support and metal nickel salt is combined as an active ingredient. By adjusting the amount and particle size of mesoporous yttrium oxide and metal nickel salt, an adsorption-enhanced nickel-based catalyst is formed.
Under low temperature conditions of 240°C, the CO2 conversion rate reached 65%, the CH4 selectivity was 100%, and it also had excellent stability, and the CO2 methanation performance was significantly improved.
Smart Images

Figure CN119500163A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of low-temperature CO2 methanation catalyst preparation, and specifically relates to an adsorption-enhanced nickel-based catalyst and a preparation method thereof and application in low-temperature CO2 methanation. Background Art
[0002] CO2 methanation reaction is one of the important routes for CO2 capture, utilization and storage. The methane product obtained by the reaction can be simply separated and incorporated into the existing natural gas pipeline network for transportation and use. Due to the great volatility of green hydrogen production and the huge problems in the storage and transportation of hydrogen, converting hydrogen into methane for storage and transportation is a very promising technology. CO2 methanation reaction can simultaneously achieve large-scale CO2 emission reduction and H2 storage. The methane produced can also reduce the external dependence of natural gas to a certain extent and alleviate the problem of shortage of natural gas resources in my country. CO2 methanation is a highly exothermic reaction, while the side reaction - reverse water gas shift reaction is an endothermic reaction. Therefore, low temperature is conducive to the high activity and high selectivity of methane preparation. In addition, metal nickel salts are easy to sinter at high temperatures, resulting in poor catalyst stability.
[0003] In order to improve the low-temperature performance and stability of the catalyst, it is necessary to rationally design the active metal and support in the catalyst. For the CO2 methanation reaction, the size of the active metal nickel salt directly affects the adsorption strength of the intermediate CO, and the CO adsorption strength is the key to evaluating the catalytic activity. Although small-sized nickel has more reaction sites, CO adsorption is weak, and the product is mainly CO; as the size of nickel increases, CO adsorption gradually increases, and the product is mainly methane. Therefore, medium-sized metal nickel salts with more reaction sites and stronger CO adsorption are the key to achieving efficient production of methane from CO2. In addition, the support effect and strong metal-support interaction also play an important role in the CO2 hydrogenation process. The support can not only promote the dispersion of active metals and provide sufficient active sites, but also adjust the adsorption strength of CO2 on the catalyst surface, thereby regulating the CO2 activation ability.
[0004] In view of this, in order to overcome the shortcomings of the existing technology, it is necessary to provide a low-temperature nickel-based CO2 methanation catalyst, so as to simultaneously improve the adsorption strength of the reactant CO2 and the intermediate CO on the catalyst surface, thereby improving the low-temperature CO2 methanation performance. Summary of the invention
[0005] One of the purposes of the present invention is to provide an adsorption-enhanced nickel-based catalyst.
[0006] The technical solution of the present invention to solve the above technical problems is: an adsorption-enhanced nickel-based catalyst, wherein the adsorption-enhanced nickel-based catalyst uses mesoporous yttrium oxide as a carrier and metal nickel salt as an active ingredient, wherein the mass content of the mesoporous yttrium oxide is 80.0-95.0wt%, and the mass content of the metal nickel salt is 5.0-20.0wt%.
[0007] The principle of the adsorption enhanced nickel-based catalyst of the present invention is:
[0008] The content of metal nickel salt and mesoporous yttrium oxide affects the activity of nickel-based catalysts and the nanometer size of metal nickel salt. When the content of metal nickel salt is too little, there are few active sites and weak adsorption performance, which leads to low catalytic activity; when the content of metal nickel salt is too high, it is easy to agglomerate on the surface of mesoporous yttrium oxide, and the particle size formed is too large, and the reaction sites are reduced, resulting in reduced activity. The present invention has proved through a large number of experiments that when the mesoporous yttrium oxide and metal nickel salt use the above-mentioned mass content, the obtained adsorption-enhanced nickel-based catalyst has the best technical effect, has excellent low-temperature CO2 methanation performance, and has a CO2 conversion rate of 65% and a CH4 selectivity of 100% under low temperature conditions of 240°C, and has excellent stability.
[0009] The beneficial effects of the adsorption-enhanced nickel-based catalyst of the present invention are:
[0010] 1. The present invention uses mesoporous yttrium oxide as a carrier, and controls the particle size of the metal nickel salt by adjusting the dosage of the metal nickel salt and the mesoporous yttrium oxide, and using the confinement effect of the mesoporous yttrium oxide, so as to achieve a higher CO2 conversion rate of the adsorption-enhanced nickel-based catalyst at low temperature.
[0011] 2. The adsorption-enhanced nickel-based catalyst of the present invention has excellent low-temperature CO2 methanation performance. Under low-temperature conditions of 240°C, the CO2 conversion rate reaches 65% and the CH4 selectivity is 100%, and it also has excellent stability.
[0012] Based on the above technical solution, the present invention can also be improved as follows.
[0013] Furthermore, the average pore size of the mesoporous yttrium oxide is 8.2 nm and the pore volume is 0.54 cm 3 / g, specific surface area is 184m 2 / g; the particle size of the metal nickel salt is 8.0-9.0nm.
[0014] The above further beneficial effects are: mesoporous yttrium oxide is a confined nickel nanoparticle structure, which strengthens the adsorption capacity of reactant CO2 and key intermediate CO, and significantly improves the low-temperature CO2 methanation performance of nickel-based catalysts. Mesoporous yttrium oxide has a large specific surface area and a porous structure, which can promote the uniform dispersion of nickel. The porous confinement effect can limit the size of nickel metal nanoparticles, and can better control the size of nickel metal.
[0015] Furthermore, the particle size of the adsorption-enhanced nickel-based catalyst is 10-200 meshes.
[0016] A second object of the present invention is to provide a method for preparing the above-mentioned adsorption-enhanced nickel-based catalyst.
[0017] The technical solution of the present invention to solve the above technical problem is: the preparation method of the above adsorption enhanced nickel-based catalyst comprises the following steps:
[0018] S1: Preparation of mesoporous yttrium oxide support
[0019] S11: Weigh yttrium salt, dissolve it in ethanol, and stir it at room temperature to obtain a first homogeneous solution; add mesoporous silica to the first homogeneous solution, stir it at room temperature for 0.5 to 1 hour, then stir it in a water bath at 30 to 40° C. to completely evaporate the ethanol, and then calcine it in an air atmosphere at 500 to 600° C. for 5 to 7 hours to obtain a white solid;
[0020] S12: transferring the obtained white solid to a sodium hydroxide solution, stirring continuously for 12 to 24 hours in a water bath, centrifuging and washing with deionized water, and repeating for 3 to 5 times; drying the precipitate obtained by centrifugation at 100 to 120° C. for 12 to 24 hours to obtain a mesoporous yttrium oxide carrier;
[0021] S2: Preparation of Precursors
[0022] Weigh a metal nickel salt, dissolve it in deionized water, and stir it thoroughly at room temperature to obtain a second homogeneous solution; slowly add the mesoporous yttrium oxide support obtained in step S1 to the second homogeneous solution, stir it to make it evenly mixed, stand it for aging at room temperature, dry it at 100-120° C. for 12-24 hours, and calcine it in an air atmosphere for 3-5 hours to obtain a precursor;
[0023] S3: Reduction of precursors
[0024] The precursor obtained from S2 is reduced at 300-600° C. in a hydrogen atmosphere at normal pressure for 4-10 hours to obtain an adsorption-enhanced nickel-based catalyst.
[0025] The principle of the preparation method of the adsorption enhanced nickel-based catalyst of the present invention is:
[0026] In step S1 of the present invention, ethanol is selected as the solvent, which can well diffuse the yttrium salt on the surface of the mesoporous silica, thereby forming yttrium oxide with a porous structure, and is conducive to evaporation by stirring in a water bath.
[0027] In step S2 of the present invention, static aging is beneficial to the deposition and dispersion of the metal nickel salt on the porous yttrium oxide, and the metal nickel salt formed by reduction is more evenly dispersed and has more reaction sites.
[0028] The stability test results of the adsorption-enhanced nickel-based catalyst obtained in step S3 of the present invention are: stable operation for 125 hours, CO2 conversion rate maintained at about 80%, methane selectivity of 100%, reaction temperature of 300°C, and pressure of 0.1MPa. This shows that the adsorption-enhanced nickel-based catalyst obtained by the present invention can also maintain good stability at a high temperature of 300°C, and can obtain a higher conversion rate at low temperatures. In contrast, most catalysts currently require 300°C or above to achieve higher CO2 methanation activity.
[0029] In summary, the present invention can achieve a CO2 methanation process with high conversion rate, high selectivity and high stability under mild conditions through the above-mentioned preparation method, and the obtained adsorption-enhanced nickel-based catalyst has high stability.
[0030] The beneficial effects of the preparation method of the adsorption enhanced nickel-based catalyst of the present invention are:
[0031] The present invention can realize a CO2 methanation process with high conversion rate, high selectivity and high stability under mild conditions. The obtained adsorption-enhanced nickel-based catalyst has high stability, simple operation, low cost, broad market prospects and is suitable for large-scale promotion and application.
[0032] Based on the above technical solution, the present invention can also be improved as follows.
[0033] Furthermore, in step S11, the yttrium salt is yttrium nitrate; the molar ratio of the yttrium salt to the mesoporous silica is 0.1 to 1.0; and the volume of the ethanol is 10 to 30 mL.
[0034] Furthermore, in step S12, the concentration of the sodium hydroxide solution is 1.0-3.0 mol / L; and the temperature of the water bath is 40-60°C.
[0035] A further beneficial effect of the above method is that the etching rate of mesoporous silicon oxide can be regulated by controlling the appropriate concentration and water bath temperature, which is conducive to forming mesoporous yttrium oxide with a regular structure.
[0036] Furthermore, in step S2, the metal nickel salt is nickel nitrate; the static aging time is 20 to 28 hours; and the calcination temperature is 450 to 600°C.
[0037] The further beneficial effect of adopting the above method is that the above-mentioned static aging time is conducive to the good deposition and dispersion of the metal nickel salt on the porous yttrium oxide, and the metal nickel salt formed by reduction is more evenly dispersed and has more reaction sites.
[0038] Too low a calcination temperature is not conducive to the formation of nickel oxide and strong metal-support interaction, while too high a calcination temperature will destroy the mesoporous structure. The present invention adopts the above calcination temperature to obtain a precursor with better technical effect.
[0039] Furthermore, in step S3, the hydrogen concentration of the hydrogen atmosphere is 5-100%, and the total flow rate is 5-50 mL / min.
[0040] The raw materials of the present invention can all be purchased commercially.
[0041] The third object of the present invention is to provide the use of the above-mentioned adsorption-enhanced nickel-based catalyst in low-temperature CO2 methanation reaction.
[0042] The beneficial effects of the application of the present invention are:
[0043] The reaction temperature of the above-mentioned adsorption-enhanced nickel-based catalyst has reached the temperature of CO2-containing exhaust gas from heavy emission industries such as thermal power plants and steel mills. It is expected to directly utilize industrial exhaust gas for low-temperature CO2 methanation reaction, and has great application prospects.
[0044] Based on the above technical solution, the present invention can also be improved as follows.
[0045] Furthermore, the specific method of the application is:
[0046] The above-mentioned adsorption enhanced nickel-based catalyst was placed in a fixed bed reactor, and a mixed reaction gas of carbon dioxide and hydrogen with a molar ratio of 1:4 was introduced at a mass space velocity of 6000-30000 mL / g -1 h -1 , reaction pressure 0.1~1.0MPa, reaction temperature 200~420℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The catalytic performance of adsorption-enhanced nickel-based catalysts with different metal loadings.
[0048] Figure 2 The catalytic performance of adsorption-enhanced nickel-based catalyst at different mass space velocities.
[0049] Figure 3 Catalytic performance of adsorption-enhanced nickel-based catalysts for 125 h CO2 methanation reaction.
[0050] Figure 4The catalytic performance of nickel-based catalysts with different supports.
[0051] Figure 5 Figure 2 shows the CO removal of nickel-based catalysts with different supports.
[0052] Figure 6 TEM image of mesoporous yttrium oxide.
[0053] Figure 7 This is the TEM image of the adsorption-enhanced nickel-based catalyst prepared in Example 3. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0055] Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or learned through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0056] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0057] The phrase "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0058] When dosage, concentration, or other value or parameter is expressed as a range, preferred range, or a range limited by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing a range of "1 to 5", the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0059] In some examples, approximate terms may correspond to the instrumental precision of the measured value. In the present specification and claims, range limits may be combined and / or interchanged. If not otherwise specified, these ranges include all sub-ranges contained therein.
[0060] The indefinite articles "a" and "an" before the elements or components of the present invention have no restrictions on the number of elements or components (i.e. the number of occurrences). Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0061] The terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described in the present invention mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0062] Unless otherwise specified, the raw materials and equipment used in the present invention can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.
[0063] In some embodiments, the present invention provides an adsorption-enhanced nickel-based catalyst, wherein the adsorption-enhanced nickel-based catalyst uses mesoporous yttrium oxide as a carrier and a metal nickel salt as an active ingredient, wherein the mass content of the mesoporous yttrium oxide is 80.0-95.0wt%, and the mass content of the metal nickel salt is 5.0-20.0wt%. Preferably, the mass content of the mesoporous yttrium oxide can be 80.0wt%, 85.0wt%, 90.0wt% or 95.0wt%, and correspondingly, the mass content of the metal nickel salt can be 20.0wt%, 15.0wt%, 10.0wt% or 5.0wt%.
[0064] In some embodiments, the average pore size of the mesoporous yttrium oxide is 8.2 nm and the pore volume is 0.54 cm 3 / g, specific surface area is 184m 2 / g; the particle size of the metal nickel salt is 8.0-9.0nm.
[0065] In some embodiments, the particle size of the adsorption enhanced nickel-based catalyst is 10-200 mesh, and can further be 10 mesh, 20 mesh, 30 mesh, 40 mesh, 50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh, 150 mesh, 160 mesh, 170 mesh, 180 mesh, 190 mesh or 200 mesh.
[0066] In one embodiment, a method for preparing an adsorption-enhanced nickel-based catalyst is provided, comprising the following steps:
[0067] S1: Preparation of mesoporous yttrium oxide support
[0068] S11: Weigh yttrium salt, dissolve it in ethanol, and stir it at room temperature to obtain a first homogeneous solution; add mesoporous silica to the first homogeneous solution, stir it at room temperature for 0.5 to 1 hour, then stir it in a water bath at 30 to 40° C. to completely evaporate the ethanol, and then calcine it in an air atmosphere at 500 to 600° C. for 5 to 7 hours to obtain a white solid;
[0069] S12: transferring the obtained white solid to a sodium hydroxide solution, stirring continuously for 12 to 24 hours in a water bath, centrifuging and washing with deionized water, and repeating for 3 to 5 times; drying the precipitate obtained by centrifugation at 100 to 120° C. for 12 to 24 hours to obtain a mesoporous yttrium oxide carrier;
[0070] S2: Preparation of Precursors
[0071] Weigh a metal nickel salt, dissolve it in deionized water, and stir it thoroughly at room temperature to obtain a second homogeneous solution; slowly add the mesoporous yttrium oxide support obtained in step S1 to the second homogeneous solution, stir it to make it evenly mixed, stand it for aging at room temperature, dry it at 100-120° C. for 12-24 hours, and calcine it in an air atmosphere for 3-5 hours to obtain a precursor;
[0072] S3: Reduction of precursors
[0073] The precursor obtained from S2 is reduced at 300-600° C. in a hydrogen atmosphere at normal pressure for 4-10 hours to obtain an adsorption-enhanced nickel-based catalyst.
[0074] In some embodiments, in the above step S11, the molar ratio of the yttrium salt to the mesoporous silica is 0.1-1.0, and can further be 0.1, 0.2, 0.4, 0.6, 0.8 or 1.0; the volume of the ethanol is 10-30 mL, and can further be 10 mL, 15 mL, 20 mL, 25 mL or 30 mL.
[0075] In some embodiments, in the above step S12, the concentration of the sodium hydroxide solution is 1.0-3.0 mol / L; and the temperature of the water bath is 40-60°C.
[0076] In some embodiments, in the above step S2, the metal nickel salt is nickel nitrate; the static aging time is 20 to 28 hours; the calcination temperature is 450 to 600°C, and can further be 450°C, 500°C, 550°C or 600°C.
[0077] In some embodiments, in the above step S3, the hydrogen concentration of the hydrogen atmosphere is 5-100%, and can further be 5%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%; the total flow rate is 5-50mL / min, and can further be 5mL / min, 10mL / min, 15mL / min,
[0078] 20mL / min, 25mL / min, 30mL / min, 35mL / min, 40mL / min, 45mL / min or 50mL / min.
[0079] In some embodiments, the present invention also provides the use of the above-mentioned adsorption-enhanced nickel-based catalyst in a low-temperature CO2 methanation reaction. The specific method of the application is: placing the adsorption-enhanced nickel-based catalyst in a fixed bed reactor, introducing a mixed reaction gas of carbon dioxide and hydrogen with a molar ratio of 1:4, and a mass space velocity of 6000 to 30000 mL g -1 h -1 , reaction pressure 0.1~1.0MPa, reaction temperature 200~420℃.
[0080] The following is a further description with reference to specific embodiments.
[0081] Example 1
[0082] S1: Preparation of mesoporous yttrium oxide support
[0083] S11: Weigh 2.55 g of yttrium nitrate hexahydrate, dissolve it in 20 mL of ethanol, and stir it at room temperature for 1 hour to obtain a first homogeneous solution; add 1.0 g of mesoporous silica to the first homogeneous solution, at which the molar ratio of yttrium nitrate hexahydrate to mesoporous silica is 0.4, and stir it at room temperature for 1 hour; then, keep stirring in a 35°C water bath to completely evaporate the ethanol, and then calcine it in an air atmosphere at 550°C for 6 hours to obtain a white solid product;
[0084] S12: The obtained solid product was transferred to a 2.0 mol / L sodium hydroxide aqueous solution, stirred continuously in a 50°C water bath for 20 h, centrifuged and washed with deionized water, and repeated 3 times. After the last washing until the washing liquid was neutral, the precipitate obtained by centrifugation was dried at 110°C for 12 h to obtain a mesoporous yttrium oxide carrier.
[0085] S2: Preparation of Precursors
[0086] Weigh 0.25 g of nickel nitrate hexahydrate, dissolve it in 2 mL of deionized water, and stir it thoroughly at room temperature to obtain a second homogeneous solution (i.e., nickel nitrate hexahydrate aqueous solution); slowly add 1.0 g of the mesoporous yttrium oxide support obtained in step S1 to the second homogeneous solution, stir to make it evenly mixed, and stand at room temperature for aging for 24 hours to obtain a light green solid, dry it at 110°C for 12 hours, and calcine it at 500°C in air atmosphere for 4 hours to obtain a precursor.
[0087] S3: Reduction of precursors
[0088] The precursor obtained from S2 was reduced at 500°C in a hydrogen atmosphere at normal pressure for 5 h to obtain an adsorption-enhanced nickel-based catalyst, named Ni@Y2O3-1.
[0089] The Ni@Y2O3-1 was granulated into 40-80 mesh and placed in a fixed bed reactor for CO2 methanation reaction. A mixed reaction gas of carbon dioxide and hydrogen with a molar ratio of 1:4 was introduced at a mass space velocity of 15000 mL / min. -1 h -1 , reaction pressure 0.1MPa, reaction temperature 200~420℃.
[0090] Example 2
[0091] The difference from Example 1 is that in step S2, the amount of nickel nitrate hexahydrate is 0.50 g. The rest is the same.
[0092] The adsorption-enhanced nickel-based catalyst obtained in this example is named Ni@Y2O3-2.
[0093] Example 3
[0094] The difference from Example 1 is that in step S2, the amount of nickel nitrate hexahydrate is 0.74 g. The rest is the same.
[0095] The adsorption-enhanced nickel-based catalyst obtained in this example is named Ni@Y2O3-3.
[0096] Example 4
[0097] The difference from Example 1 is that in step S2, the nickel nitrate hexahydrate is 1.0 g. The rest is the same. The adsorption-enhanced nickel-based catalyst obtained in this example is named Ni@Y2O3-4.
[0098] Comparative Example 1
[0099] The carrier of this comparative example adopts the mesoporous silica of the prior art, instead of the mesoporous yttrium oxide carrier prepared in step S1 of embodiment 3, that is, step S1 of embodiment 3 is omitted. The specific method is:
[0100] Weigh 0.74 g of nickel nitrate hexahydrate, dissolve it in 8 mL of deionized water and stir it at room temperature to obtain a nickel nitrate hexahydrate aqueous solution; slowly add 1.0 g of mesoporous silica carrier to the nickel nitrate hexahydrate aqueous solution, stir it to make it evenly mixed, stand it at room temperature for aging for 24 hours to obtain a light green solid, dry it at 110° C. for 12 hours, and calcine it at 500° C. in an air atmosphere for 4 hours to obtain a precursor. The reduction and application of the remaining precursors are the same as in Example 3.
[0101] The nickel-based catalyst obtained in this comparative example is named Ni@mesoporous silica.
[0102] Comparative Example 2
[0103] The carrier of this comparative example adopts the commercial yttrium oxide carrier of the prior art, instead of the mesoporous yttrium oxide carrier prepared in step S1 of Example 3, that is, step S1 of Example 3 is omitted. The specific method is:
[0104] Weigh 0.74 g of nickel nitrate hexahydrate, dissolve it in 2 mL of deionized water and stir it at room temperature to obtain a nickel nitrate hexahydrate aqueous solution; slowly add 1.0 g of commercial yttrium oxide carrier to the nickel nitrate hexahydrate aqueous solution, stir it to make it evenly mixed, stand it at room temperature for aging for 24 hours to obtain a light green solid, dry it at 110° C. for 12 hours, and calcine it at 500° C. in an air atmosphere for 4 hours to obtain a precursor. The reduction and application of the remaining precursors are the same as in Example 3.
[0105] The nickel-based catalyst obtained in this comparative example is named Ni / Y2O3.
[0106] The CO2 conversion rate and CH4 selectivity of the catalysts prepared in Examples 1-4 and Comparative Examples 1-2 for low-temperature CO2 methanation reaction are shown in Table 1.
[0107] Table 1 CO2 conversion and CH4 selectivity of various catalysts for low-temperature CO2 methanation reaction
[0108]
[0109] Table 1 shows the CO2 conversion rate and CH4 selectivity of each catalyst in the low-temperature CO2 methanation reaction. By comparing the examples with the comparative examples, it is found that the Ni@Y2O3-3 catalyst in Example 3 has the best low-temperature CO2 methanation activity, with a CO2 conversion rate of 65% and a methane selectivity of 99.8% at 240°C.
[0110] Experimental Results 2
[0111] The low-temperature CO2 methanation performance of the adsorption-enhanced nickel-based catalyst (Ni@Y2O3-3) prepared in Example 3 is compared with that of similar catalysts reported in the prior art, as shown in Table 2.
[0112] Table 2 Comparison of low-temperature CO2 methanation performance of adsorption-enhanced nickel-based catalysts and similar reported catalysts
[0113]
[0114] As can be seen from Table 2, the adsorption-enhanced nickel-based catalyst (Ni@Y2O3-3) prepared in Example 3 can achieve a CO2 conversion rate of 65% at a low temperature of 240°C, while other similar catalysts generally have a CO2 conversion rate of only about 30% at a similar reaction temperature. The temperature required to achieve a similar CO2 conversion rate exceeds 300°C, which reflects the excellent low-temperature CO2 methanation activity of the adsorption-enhanced nickel-based catalyst.
[0115] Experimental Results 3
[0116] The CO2 adsorption performance of the catalysts of Example 3 and the comparative example is shown in Table 3.
[0117] Table 3 CO2 adsorption performance of adsorption-enhanced nickel-based catalyst and comparative catalyst
[0118]
[0119] As shown in Table 3, the adsorption-enhanced nickel-based catalyst Ni@Y2O3-3 prepared in Example 3 has a CO2 adsorption capacity of up to 1519 μmol˙g -1 , which is much higher than that of Ni@mesoporous silica prepared in Comparative Example 1 (797.5 μmol˙g -1 ) and Ni / Y2O3 (910.1 μmol˙g -1) of CO2 adsorption. In addition, especially in the reaction temperature range of weakly adsorbed CO2 and moderately strongly adsorbed CO2, the adsorption amount of the adsorption-enhanced nickel-based catalyst Ni@Y2O3-3 prepared in Example 3 (1300.8 μmol˙g -1 ) are Ni@mesoporous silica (491.9 μmol˙g -1 ) and Ni / Y2O3 (464.0 μmol˙g -1 ) by 2.6 and 2.8 times. This indicates that the adsorption-enhanced nickel-based catalyst Ni@Y2O3-3 prepared in Example 3 has a very strong CO2 adsorption capacity, which is mainly due to the strong alkalinity of yttrium oxide itself and the large specific surface area and rich pore structure of the catalyst.
[0120] Experimental Results 4
[0121] The parameter characterization data of the catalysts in each example are shown in Table 4. The mesoporous yttrium oxide is the mesoporous yttrium oxide carrier obtained in step S12 of Example 1, and the specific surface areas and various parameters of Examples 1-4 and Comparative Examples 1-2 are parameter data of the catalysts after loading active nickel.
[0122] Table 4 Catalyst parameter characterization data of examples and comparative examples
[0123]
[0124] It can be seen from Table 4 that the pore volume and average pore size of the mesoporous yttrium oxide in Examples 1-4 are reduced after the active nickel metal is loaded, indicating that part of the active metal is filled or loaded in the mesopores, and the particle size of the active metal nickel salt is controlled at 8-8.5 nm. Compared with the data of Comparative Example 2, it is found that the use of mesoporous yttrium oxide as a carrier can well control the particle size of the active metal nickel salt, thereby improving the catalytic activity of the catalyst.
[0125] Figure 1 A comparison of the reaction results of the adsorption-enhanced nickel-based catalysts with different metal loadings in Examples 1-4 in the range of 200-420°C is given. It can be seen that the Ni@Y2O3 catalyst can catalyze the CO2 methanation reaction at 200°C. As the metal loading increases, the low-temperature activity of the catalyst gradually increases, and the activity reaches the highest when the nickel content reaches more than 15%.
[0126] Figure 2 The best embodiment 3 catalyst is given at 240 ° C, 15000 ~ 30000mLg -1 h -1 The low-temperature CO2 methanation performance within the space velocity range shows that the Ni@Y2O3 catalyst can still maintain a high CO2 conversion rate and a CH4 selectivity close to 100% at high space velocity.
[0127] Figure 3 The optimal embodiment 3 catalyst is given at 300°C, 0.1MPa, 15000mLg -1 h -1 The long-term operation stability under reaction conditions shows that even at a high temperature of 300°C, the catalyst performance can remain stable, with a CO2 conversion rate of 80% and a CH4 selectivity of 100%.
[0128] Figure 4 The catalytic performance of the catalysts of Example 3 and Comparative Examples 1-2 are given. It can be seen that no matter whether mesoporous silica or commercial Y2O3 is used as the carrier, the overall CO2 methanation performance of the catalyst, especially the low-temperature performance is far inferior to that of the catalyst of Example 3. At 240°C, the CO2 conversion rates of the catalysts of Comparative Example 1 and Comparative Example 2 are only 2.2% and 1.8%, respectively. To achieve a CO2 conversion rate of more than 60%, the catalysts of Comparative Example 1 and Comparative Example 2 require high temperatures of 280°C and 340°C, respectively, which illustrates the superiority of the catalyst of Example 3 in low-temperature CO2 methanation reactions.
[0129] Figure 5 The CO desorption results of the catalysts of Example 3 and Comparative Example 1 are given. It can be seen that the relative intensity of CO species adsorbed on the surface of the catalyst of Example 3 is almost unchanged after being purged for 3 hours, while the relative intensity of CO species adsorbed on the surface of the catalyst of Comparative Example 1 is reduced by more than 60% after being purged for 3 hours, indicating that the catalyst of Example 3 also has extremely strong CO adsorption capacity.
[0130] Figure 6 TEM image of a mesoporous yttrium oxide carrier. It can be seen from the image that the mesoporous yttrium oxide carrier obtained by the method of the present invention has an ordered mesoporous structure with a regular structure.
[0131] Figure 7 This is a TEM image of the adsorption-enhanced nickel-based catalyst prepared in Example 3. It can be seen from the figure that the mesoporous yttrium oxide loaded with active metals maintains the original structural morphology, and the particle size distribution of the active nickel metal is very concentrated, indicating that the particle size is uniform and the mesoporous yttrium oxide has good control over the particle size of the active metal nickel salt.
[0132] In summary, the adsorption-enhanced nickel-based catalyst of the present invention has extremely strong adsorption capacity for both the reactant CO2 and the intermediate CO, which is beneficial to the conversion of CO2 to CH4 via CO, and therefore has excellent low-temperature CO2 methanation activity.
[0133] References:
[0134] 1.Y.Li,Y.Men,S.Liu,J.Wang,K.Wang,Y.Tang,W.An,X.Pan,L.Li,Remarkablyefficient and stable Ni / Y2O3 catalysts for CO2 methanation:Effect of citricacid addition,Appl.Catal.B-Environ.293(2021)120206.
[0135] 2.Q.Liu,S.Wang,S.Lv,F.Han,J.Ouyang,High Stability of the Ni-YCe / Diatomite catalyst for CO2 methanation:The synergistic coupling of citricacid and Y2O3,ACS Sustainable Chem.Eng.11(2023)12946-12958.
[0136] 3.C.Italiano,J.Llorca,L.Pino,M.Ferraro,V.Antonucci,A.Vita,CO and CO2methanation over Ni catalysts supported on CeO2,Al2O3 and Y2O3 oxides,Appl.Catal.B-Environ.264(2020)118494.
[0137] 4.Y.Yan,Y.Dai,Y.Yang,A.A.Lapkin,Improved stability of Y2O3 supportedNi catalysts for CO2 methanation by precursor-determined metal-supportinteraction,Appl.Catal.B-Environ.,237(2018)504-512.
[0138] 5.RAEl-Salamony,SAEl-Sharaky,SAAl-Temtamy,AMAl-Sabagh,HMKilla,CO2 valorization into synthetic natural gas (SNG) using a Co–Nibimetallic Y2O3 based catalysts.Int.J.Chem.React.Eng.19(2021)571-583.
[0139] 6.X.Fang, L.Xia, S.Li, Z.Hong, M.Yang,
[0140] The parts of the technical scope of the present invention that are not exhausted by the midpoint value of the embodiment and the new technical solutions formed by the equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope of protection claimed by the present invention, and unless otherwise specified, there is no unique and irreplaceable combination between all the parameters involved in the solutions of the present invention.
[0141] It is easy for those skilled in the art to understand that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An adsorption-enhanced nickel-based catalyst, characterized in that: The adsorption-enhanced nickel-based catalyst uses mesoporous yttrium oxide as a carrier and metal nickel salt as an active ingredient, wherein the mass content of the mesoporous yttrium oxide is 80.0-95.0wt%, and the mass content of the metal nickel salt is 5.0-20.0wt%.
2. The adsorption-enhanced nickel-based catalyst according to claim 1, characterized in that: The average pore size of the mesoporous yttrium oxide is 8.2 nm and the pore volume is 0.54 cm 3 / g, specific surface area is 184m 2 / g; the particle size of the metal nickel salt is 8.0-9.0nm.
3. The adsorption-enhanced nickel-based catalyst according to claim 1, characterized in that: The particle size of the adsorption enhanced nickel-based catalyst is 10-200 meshes.
4. A method for preparing an adsorption-enhanced nickel-based catalyst according to any one of claims 1 to 3, characterized in that: The steps include: S1: Preparation of mesoporous yttrium oxide support S11: Weigh yttrium salt, dissolve it in ethanol, and stir it at room temperature to obtain a first homogeneous solution; add mesoporous silica to the first homogeneous solution, stir it at room temperature for 0.5 to 1 hour, then stir it in a water bath at 30 to 40° C. to completely evaporate the ethanol, and then calcine it in an air atmosphere at 500 to 600° C. for 5 to 7 hours to obtain a white solid; S12: transferring the obtained white solid to a sodium hydroxide solution, stirring continuously for 12 to 24 hours in a water bath, centrifuging and washing with deionized water, and repeating for 3 to 5 times; drying the precipitate obtained by centrifugation at 100 to 120° C. for 12 to 24 hours to obtain a mesoporous yttrium oxide carrier; S2: Preparation of Precursors Weigh a metal nickel salt, dissolve it in deionized water, and stir it thoroughly at room temperature to obtain a second homogeneous solution; slowly add the mesoporous yttrium oxide support obtained in step S1 to the second homogeneous solution, stir it to make it evenly mixed, stand it for aging at room temperature, dry it at 100-120° C. for 12-24 hours, and calcine it in an air atmosphere for 3-5 hours to obtain a precursor; S3: Reduction of precursors The precursor obtained from S2 is reduced at 300-600° C. in a hydrogen atmosphere at normal pressure for 4-10 hours to obtain an adsorption-enhanced nickel-based catalyst.
5. The method for preparing an adsorption-enhanced nickel-based catalyst according to claim 4, characterized in that: In step S11, the yttrium salt is yttrium nitrate; the molar ratio of the yttrium salt to the mesoporous silica is 0.1 to 1.0; and the volume of the ethanol is 10 to 30 mL.
6. The method for preparing an adsorption-enhanced nickel-based catalyst according to claim 4 or 5, characterized in that: In step S12, the concentration of the sodium hydroxide solution is 1.0-3.0 mol / L; the temperature of the water bath is 40-60°C.
7. The method for preparing an adsorption-enhanced nickel-based catalyst according to claim 4 or 5, characterized in that: In step S2, the metal nickel salt is nickel nitrate; the static aging time is 20 to 28 hours; and the calcination temperature is 450 to 600°C.
8. The method for preparing an adsorption-enhanced nickel-based catalyst according to claim 4 or 5, characterized in that: In step S3, the hydrogen concentration of the hydrogen atmosphere is 5-100%, and the total flow rate is 5-50 mL / min.
9. Use of the adsorption-enhanced nickel-based catalyst according to any one of claims 1 to 3 or the adsorption-enhanced nickel-based catalyst prepared by the preparation method according to any one of claims 4 to 8 in low-temperature CO2 methanation reaction.
10. The use according to claim 9, characterized in that: The specific application method is: placing the adsorption-enhanced nickel-based catalyst according to any one of claims 1 to 3 or the adsorption-enhanced nickel-based catalyst prepared by the preparation method according to any one of claims 4 to 8 in a fixed bed reactor, introducing a mixed reaction gas of carbon dioxide and hydrogen with a molar ratio of 1:4, and a mass space velocity of 6000 to 30000 mL / g -1 h -1 , reaction pressure 0.1~1.0MPa, reaction temperature 200~420℃.
Citation Information
Patent Citations
Preparation method of methanation catalyst doped with rare earth Y
CN107519858A
Preparation method of solvent-free high-activity loaded metal nickel catalyst and application thereof
CN108067285A
Nickel-based catalyst for dry reforming of methane and carbon dioxide and preparation method and application thereof
CN109759074A
Carbon dioxide methanation catalyst and preparation method thereof
CN117942972A
Catalyst for the methanation of syngas and producer gas
US20200094227A1